Grief: the biography of a Holocaust photograph - Shneer, David (Oxford University Press, 2020)
Grief: The Biography of a Holocaust Photograph presents never-before-seen images and an untold story about a Soviet photographer and his signature image. David Shneer tells the story of how World War II photojournalist Dmitri Baltermants transformed a news photograph of a grieving woman at the first liberation of a German mass atrocity site into a transcendentally human tragedy that today appears in Holocaust archives and art museums around the world.